Effects of site of origin, time of seed maturation, and seed age on germination behavior of Portulaca oleracea from the Old and New Worlds - El-Keblawy, A.; Al-Ansari, F.
The effects of site of origin, time of seed maturation, and seed age on germination behavior, in terms of final percentage of germination and time for 50
Keywords: DORMANCY; GEOGRAPHICAL REGIONS; GERMINATION; GERMINATION RATE; PORTULACA OLERACEA; SEED AGE; SITE OF ORIGIN; TIME OF SEED MATURATION